Measuring innovative capability maturity model of trucking companies in Indonesia - Kyatmaja Lookman; Nyoman Pujawan; Reny Nadlifatin (Cogent Business & Management, 2022)
Trucking companies are important part of supply chains, as they connect most of product movements. While a lot of studies have been done to assess supply chain maturity level, very limited studies have been done to specifically address trucking companies. In this study we develop a model and measurement instruments to assess maturity of trucking companies in terms of their innovative capabilities. Innovative capabilities are critical in today's fast technological development such as industry 4.0 and trucking companies have opportunities to use those technologies to play a better role in the supply chain they involve in. We then use the instruments to assess the maturity level of 52 companies that involved in transporting goods using trucks. The results show that the maturity level has a widespread, ranging from the lowest to the highest level, but most of them are in the category of partial maturity to mature. This indicates that most companies have an opportunity to improve their innovative capabilities.
Keywords: 650; market orientation; innovative capability; Maturity model; supplier relationship; technological capability